The significance of IPv6 research lab activity in enhancing teaching and learning of IPv6 deployment - Hamid, Erman; Masud, Mohd Zaki; Mat Ariff, Nor Azman; Abdollah, Mohd Faizal; Bahaman, Nazrulazhar (2010)
IPv6 is the next generation of Internet Protocol for the network. Introduced in early 1990 by Engineering Task Force Internet (E1TF), IPv6 will become the Alternative solution for the current Internet protocol (1Pv4) addressing limitation problems. After the era of IPv4, IPv6 will be fully implemented as the addressing internet protocol. Even though the need on IPv6 is very demanding, it still not widely implemented in Malaysia. This is due to the lack of promotion and personnel to implement IPv6. The responsibility has now fallen upon the university to develop and train experts for IPv6 implementation. In order to effectively train experts there is needs to develop working laboratories that enable students to learn IPv6 with a systematic approach. Due to that reason this paper presents a study on the need of an IPv6 lab, namely IPv6RG lab in Universiti Teknikal Malaysia Melaka (UTeM). This lab will act as the training center for students to experience the latest tools and software in designing, developing and testing the implementation of IPv6.